Spiritism and psychiatry - Ascari, Pierpaolo (Scenari, 2021)
The article intends to show what is the function that nineteenth-century French psychiatry attributes to images. The encounter between doctors and images has nothing episodic at all, but it would seem preparatory to the very birth of psychiatric knowledge, the affirmation of which will then be characterized by the frequent mobilization of painting, physiognomy, history of art and photography. In this effort, however, psychiatry itself reveals itself as a "science of the unknown", according to the famous definition of Jurgis Baltrušaitis, which "the more it subtler, the more it purifies its own notions, the more it strives to give itself solid foundations, the more he gets lost in the fantastic ". An exemplary case of this reversal is provided by the relationships between spiritualism, popular religiosity (with reference to the first pilgrimages to the sanctuary of Lourdes) and the work carried out by the images in an attempt to prove the legitimacy of the diagnoses and tools. therapeutic. In the end, the image turns out to be ambivalent, because together and through the figurative organization of the symptom it reveals what are the power relationships that have placed it in the foreground. With reference to authors such as Michel Foucault, Georges Didi-Huberman or Claude Quétel, the article intends to outline a genealogy of these correlations and the meaning they can assume in the more general definition of aesthetic experience on the literature of the time